Hardly seen, often heard: acoustic presence of harbour porpoises (Phocoena phocoena) in one of the most urbanised estuaries in the world - Rekdahl, Melinda L.; Trabue, Sarah G.; King-Nolan, Carissa D.; Strindberg, Samantha; Rosenbaum, Howard C. (Frontiers in Marine Science, 2023)
The New York-New Jersey (NY-NJ) Harbour Estuary and surrounding waters support the largest port along the U.S. East Coast, commercial and recreational fishing, and a burgeoning offshore wind energy industry. Despite the high level of anthropogenic use, cetacean sightings have increased in recent years. Here, we investigated the spatiotemporal distribution of harbour porpoise in the NY-NJ Harbour Estuary from 2018–2020 using six archival acoustic recorders. Generalised additive mixed models were used to explore the relationship between weekly harbour porpoise presence and environmental variables. Harbour porpoises were detected at low levels year-round, with seasonal peaks in presence in winter to spring (February to June). Sea surface temperature and chlorophyll-a concentration were significant predictors of harbour porpoise presence, although the relationship warrants further investigation. Our results provide valuable insight into harbour porpoise distribution in the NY-NJ Harbour Estuary, which is likely related to oceanographic processes affecting prey availability. This information is timely for informing mitigation and management actions for forthcoming offshore wind energy development. Harbour porpoises are vulnerable to a range of anthropogenic impacts that have led to population declines in other regions, and therefore further research efforts are recommended for the NY-NJ Harbour Estuary and greater New York Bight.